Endocrine and hypothalamic outcomes following transsphenoidal and transcranial surgery in selected paediatric patients with craniopharyngiomas are comparable. (4th April 2011) - Ikazoboh, E C; Deniz, K; Mankad, K; Saunders, D; Powell, M; Dattani, M; Spoudeas, H A
Abstract : Aim: To compare long term outcomes following transsphenoidal surgery (TSS) and transcranial surgery (TCS) in paediatric patients with craniopharyngiomas treated at a single institution. Methods: The medical records and imaging studies of 21 patients (age <18 years at time of surgery) with pathologically proven craniopharyngioma diagnosed between 1995 and 2009 were identified and retrospectively analysed. 10 patients (7 males) underwent TSS and were followed-up after a mean duration of 63.75 months (range 6–128 months). Six of the TSS were performed at primary diagnosis and four at recurrence; two patients in the latter group who died from tumour related causes were excluded from further analysis. 11 patients (7 males) underwent TCS and were followed-up after a mean duration of 74.8 months (12–145 months). Patients in each treatment group were matched for gender and age at diagnosis. Results: All 19 patients analysed had at least some sellar component to their tumour. The mean (mid-line) tumour height based on MRI at presentation was 27.0 mm prior to TSS and 43.85 mm prior to TCS. Complete tumour resection was achieved in two patients (one patient each following TSS and TCS). 16 patients had adjuvant radiotherapy: 6 (75.0%) following TSS and 10 (90.9%) following TCS. Eight patients experienced tumour recurrence: four (50.0%) following TSS (two of which were performed as secondary procedures), and four (36.4%) following TCS. Of the eight patients who had TSS, four (50.0%) had no pituitary deficit and one (12.5%) had panhypopituitarism at presentation (8 (72.7%) and 0 respectively for patients who had TCS). At last follow-up, all patients who had TSS had at least one pituitary hormone deficiency, GHD being the most prevalent (100%), and DI the least prevalent (50%) (compared with 72.7% and 36.4% respectively for patients who had TCS). Following TSS, four (50%) patients had panhypopituitarism with DI, compared with five (45.5%) following TCS. Mean body mass index at last follow-up was +1.51 SDs (range −0.79 to +3.35) following TSS and +2.37 SDs (+0.862 to +3.76) following TCS. Conclusion: TSS in selected paediatric patients with craniopharyngioma is safe and is associated with endocrine and hypothalamic outcomes that are comparable to outcomes following TCS.